EFFECT OF NON-GENETIC FACTORS ON REPRODUCTIVE TRAITS IN SIMMENTAL COWS REARED IN SUBTROPICAL CLIMATE CONDITION - M. Bolacali; Y. Öztürk (Journal of Animal and Plant Sciences, 2017)
This study aimed to determine reproductive traits, such as gestation length (GL), service period (SP), calving interval (CI), number of insemination per pregnancy (NIPC), and first calving age (FCA) and to reveal the non-genetic parameters affecting these traits in Simmental cows raised at a private farm in Çorum Province under subtropical climate conditions according to Trewartha climate grading and Csb based on the Köppen–Geiger system. A total of 1904 reproduction performance records of 706 Simmental cows raised between 2001 and 2014 were utilized in this study. The GL, SP, CI, NIPC, and FCA were 283.19 days, 116.41 days, 394.30 days, 1.75, and 847.0 days, respectively, for the Simmental cows in the study. The effects of calving year (P<0.001), lactation parity (P<0.05), calving age (P<0.001), birth type (P<0.001) and parity (P<0.001) on GL were significant. Among the factors affecting SP, the effects of calving year and calving season were significant (P<0.01). Calving year, lactation parity, and calving season were significant at different levels for CI. Among the evaluated factors affecting NIPC, calving year, lactation parity, calving season, calving age, and calving year had significant effects (P<0.001, P<0.05). Year, calving age, and calving season were significant (P<0.001) for FCA. As the values for reproductive traits, namely, GL, SP, CI, NIPC, and FCA, were generally within standard values for the Simmental cows, herd management programs seemed to be properly performed at the farm where the study was conducted. Moreover, Simmental cows were successfully raised under subtropical climate conditions.
Keywords: cattle; fertility traits; non-genetic factors; Simmental